2004
DOI: 10.1097/00001756-200403010-00033
|View full text |Cite
|
Sign up to set email alerts
|

Proton magnetic resonance spectroscopy in anorexia nervosa: correlations with cognition

Abstract: The aim of this study was to investigate the relationship between cognitive impairment and cerebral metabolites in patients with anorexia nervosa (AN). N-acetylaspartate (NAA), creatine/phosphocreatine (Cr), choline-containing compounds, glutamate/glutamine (Glx) and myoinositol were measured by proton magnetic resonance spectroscopy (H-MRS) of the left prefrontal cortex. Compared with healthy controls, AN patients displayed a significantly poorer performance in verbal learning and in attentional and executive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 21 publications
5
51
2
Order By: Relevance
“…It is of note that elevated homocysteine levels have been associated with better short-and long-term verbal memory performance in females with anorexia nervosa and bulimia nervosa [15] . A significant reduction in glutamate/glutamine levels has also been observed in anorectic patients [43] .…”
Section: Discussionmentioning
confidence: 85%
“…It is of note that elevated homocysteine levels have been associated with better short-and long-term verbal memory performance in females with anorexia nervosa and bulimia nervosa [15] . A significant reduction in glutamate/glutamine levels has also been observed in anorectic patients [43] .…”
Section: Discussionmentioning
confidence: 85%
“…50) These changes may be related to decline of cognitive functioning. 51) There are reports that impairment of memory-related behavior and reduced anxiety behavior results from PM in rats. 12,[20][21][22] We have also previously reported alterations in cognitive function in PM mice.…”
Section: Discussionmentioning
confidence: 99%
“…A recent 1 H-MRS study of 11 unmedicated female AN patients reported reduced dorsolateral prefrontal cortex myo-inositol relative to healthy controls, inversely correlating this reduction with duration of illness (Ohrmann et al, 2004). In an earlier 1 H-MRS study of 20 patients with AN or BN, reduced frontal white matter myo-inositol concentrations were found in patients compared with healthy controls, with those patients with the lowest body mass index having the greatest reductions (Roser et al, 1999).…”
Section: Eating Disordersmentioning
confidence: 92%